2010
DOI: 10.1016/j.ijsu.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hydatid disease: Is capitonnage mandatory following cystotomy?

Abstract: Pulmonary hydatid disease still remains an important healthcare problem. Conservative operative interventions including cystotomy or cystotomy with capitonnage are the two commonly used techniques. There is still significant controversy, however, over selection of these two procedures. In this retrospective analysis of 66 patients with hydatid disease, we employed three types of interventions, Group A, (n = 5) cystotomy alone with closure of bronchial openings; Group B, (n = 54) cystotomy with capitonnage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…There is concern of capitonnage sutures leading to infection and laceration of the pulmonary tissue especially in infected and complicated cysts and as such controversy persists as to the need for capitonnage. While several authors looking at both uncomplicated and complicated hydatid cysts have shown no difference in rates of post-operative air leak and infection with or without capitonnage (68-70), there have been multiple more recent reports of increased complication rates (prolonged air leaks, abscess formation) associated with the practice of not performing capitonnage (71)(72)(73). The practice at the authors' unit has been to meticulously look for and close all bronchial openings and then drain the cyst adequately through a dependent cystotomy.…”
Section: Technique Of Enucleationmentioning
confidence: 99%
“…There is concern of capitonnage sutures leading to infection and laceration of the pulmonary tissue especially in infected and complicated cysts and as such controversy persists as to the need for capitonnage. While several authors looking at both uncomplicated and complicated hydatid cysts have shown no difference in rates of post-operative air leak and infection with or without capitonnage (68-70), there have been multiple more recent reports of increased complication rates (prolonged air leaks, abscess formation) associated with the practice of not performing capitonnage (71)(72)(73). The practice at the authors' unit has been to meticulously look for and close all bronchial openings and then drain the cyst adequately through a dependent cystotomy.…”
Section: Technique Of Enucleationmentioning
confidence: 99%
“…The majority of the cysts (71.1%) were in the right side of the lung and lower lobes were more commonly affected, in line with the literature. [3,4,[8][9][10] The gold standard for managing PHCs of any size is lungconservation surgery. This ensures that the maximum amount of viable lung is maintained while ensuring complete removal of all viable parasite material.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures that the maximum amount of viable lung is maintained while ensuring complete removal of all viable parasite material. [2][3][4][5][6][7][8]10] Different surgical procedures have been described in the literature, such as enucleation (Ugon method) with or without capitonnage, [4] pericystectomy (Perez-Fontana method), [5] cystotomy with capitonnage (Barrett's method), [2] cystostomy with the closure of the bronchial openings alone, [11] open aspiration by the Figuera technique, [10] and lung resection (i.e. wedge resection, segmentectomy and lobectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Nabi et al proposed it is difficult to close the bronchial openings in ruptured or infected cysts and found all of them had postoperative prolonged air leak due to cut-through of sutures leading to empyema formation. The addition of capitonnage had the advantage of securing unidentified air leaks during surgery [22].…”
Section: Discussionmentioning
confidence: 99%